2020
DOI: 10.3390/molecules25040978
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan-Inspired Biomaterials for the Development of Bioactive Hydrogel Networks

Abstract: Glycosaminoglycans (GAG) are long, linear polysaccharides that display a wide range of relevant biological roles. Particularly, in the extracellular matrix (ECM) GAG specifically interact with other biological molecules, such as growth factors, protecting them from proteolysis or inhibiting factors. Additionally, ECM GAG are partially responsible for the mechanical stability of tissues due to their capacity to retain high amounts of water, enabling hydration of the ECM and rendering it resistant to compressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 242 publications
(418 reference statements)
0
31
0
Order By: Relevance
“…Glycosaminoglycans (GAGs) are a class of long unbranched periodic negatively charged polysaccharides found in ECM that take part in many biological processes such as anticoagulation, angiogenesis and tissue regeneration (Walimbe & Panitch, 2019 ; Bojarski et al., 2020 ). They are partially responsible for the mechanical stability of tissues due to their capacity to retain a large quantity of water, enabling hydration of the ECM and rendering it resistant to compressive forces (Neves et al., 2020 ). Results of the GAGs and collagen assays indicated that the decellularization process did not lead to loss of collagen or GAG concentrations of the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosaminoglycans (GAGs) are a class of long unbranched periodic negatively charged polysaccharides found in ECM that take part in many biological processes such as anticoagulation, angiogenesis and tissue regeneration (Walimbe & Panitch, 2019 ; Bojarski et al., 2020 ). They are partially responsible for the mechanical stability of tissues due to their capacity to retain a large quantity of water, enabling hydration of the ECM and rendering it resistant to compressive forces (Neves et al., 2020 ). Results of the GAGs and collagen assays indicated that the decellularization process did not lead to loss of collagen or GAG concentrations of the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nonhealing chronic bone tissue defects represent a major problem in healthcare. Despite numerous reports [ 1 , 2 ], there is still a growing need to identify new high-impact compounds for bone tissue regeneration applications. A current approach for bone tissue engineering is based on scaffolds that release growth factors (GFs) required for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels and nanogels can be prepared using synthetic [26][27][28] or natural polymers [29][30][31][32] or peptide sequences. 33,34 With respect to polymers, peptides exhibit several advantages such as high biocompatibility, biodegradability and tunability.…”
Section: Introductionmentioning
confidence: 99%